2019
DOI: 10.1002/jclp.22754
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering important outcomes of the nonsuicidal self‐injury disorder diagnostic criterion A

Abstract: Objective: The nonsuicidal self-injury (NSSI) disorder diagnostic criteria have been the focus of empirical study.However, Criterion A (i.e., required frequency and timeframe) has received relatively limited attention. The current study aimed to examine the relationship between past 12-month NSSI frequency and eight NSSI behavior features among individuals with past 12-month and 1-month NSSI.Method: Participants were 723 undergraduate students reporting at least 1 past 12-month NSSI act and completed online qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…This could potentially increase utility in clinical samples. One such attempt was made by Muehlenkamp et al (18), who investigated differences between groups with low (1-4), moderate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and high (≥25) NSSI frequency.…”
Section: Psychopathology and Traumatic Experiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…This could potentially increase utility in clinical samples. One such attempt was made by Muehlenkamp et al (18), who investigated differences between groups with low (1-4), moderate (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and high (≥25) NSSI frequency.…”
Section: Psychopathology and Traumatic Experiencesmentioning
confidence: 99%
“…Since the criteria were published, they have been subject to discussion (e.g., 6,8,[16][17][18][19]. Based on recent empirical data, revisions of the criteria have been suggested, including proposals that a dimensional approach to the disorder would be more beneficial (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Namely, studies that evaluated criterion A found mixed evidence as to whether engaging in NSSI for five days in the past year is a clinically meaningful and valid benchmark (Ammerman et al, 2019;Muehlenkamp et al, 2017). It has been suggested that the current fivedays-specifier is too lenient and possibly over-diagnoses those who experiment with NSSI or intermittently engage in the behaviour (Muehlenkamp and Brausch, 2016).…”
Section: Introductionmentioning
confidence: 99%